Effects of imperatorin on airway remodeling in bronchial asthma through S1PR2/STAT3 signaling pathway: Effect of Imperatorin on airway remodeling in bronchial asthma - Wang, Dandan; Cui, Yunmei; Gao, Fan; Zheng, Weiwei; Li, Jinzi; Xian, Zhemin (Cellular and Molecular Biology, 2023)
In this study, we analyzed the effect of Imperatorin (IMP) on airway remodeling in bronchial asthma (BA) through the S1PR2/STAT3 signaling pathway. First, 30 BALB/c mice were randomized into control, model, and intervention groups. The control group was left untreated; the model and intervention groups were BA modeled and; the intervention group was further intraperitoneally injected with IMP following modeling. Lung tissue pathological changes, inflammatory cell deposition in bronchoalveolar lavage fluid (BALF), expression of inflammatory factors, and oxidative stress (OS) were detected in three groups of mice. We found that the intervention group had reduced macrophage and lymphocyte counts in BALF and ameliorated pathological damage of lung tissue than the control group after intervention. In addition, the post-interventional inflammatory factors and malonaldehyde (MDA) in the intervention group were elevated compared with the control group but reduced versus the model group, while the superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) were lower than those in the control group and higher compared with the model group (P<0.05). In addition, the expression of S1PR2/STAT3 pathway in three groups of mice showed that S1PR2/STAT3 signaling was activated in the model group, while the expression of S1PR2 and STAT3 in the intervention group was lower than that in the model group (P<0.05). These results demonstrate that IMP reverses pathological injury in BA and alleviates airway remodeling by inhibiting the S1PR2/STAT3 axis.